Azalea Caterpillar, Datana major Grote & Robinson (Insecta: Lepidoptera: Notodontidae) - G. W. Dekle; Thomas R. Fasulo (EDIS)
The azalea caterpillar, Datana major G & R, is found in Florida from July through October on azaleas (Rhododendron spp.). Often, the caterpillars completely defoliate much of the plant before they are detected. While the caterpillar appears hairy, it is harmless to humans and can be picked off the bushes by hand. This document is EENY-137 (originally published as DPI Entomology Circular No. 6), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: June 2000.